Single vs. Multiple-Item Scales for Measuring Religious Values - Gorsuch, Richard L. (Journal for the scientific study of religion, 1972)
Investigators must choose between single and multiple-item scales of religiosity. To aid in that decision, single and multiple measures were compared to determine whether they covered the same areas and formed relationships with variables from another domain. The results suggest that single-item scales (e.g., the Christological confession and the rated importance of religion) are good measures of an intrinsic proreligious position but that multiple-item scales are better measures of traditional Christian Orthodoxy. The discussion points out conditions when the less expensive but less valid measure is to be chosen over the more valid but more expensive scale.